The impact of 4-nonylphenol on the expression of the vitellogenin gene and the alterations in steroid hormones in male Sobaity seabream (Sparidentex hasta) - Golchin Manshadi, Alireza; Negintaji, Zahra; Shirazi, Amirhossein Rezazadeh (Journal of Fisheries, 2026)
The study aimed to investigate the effects of 4-nonylphenol exposure on the expression of the vitellogenin gene (Vg) and sexual steroid hormones in male Sobaity seabream (Sparidentex hasta). A total of 78 fish individuals were randomly assigned to six tanks, receiving doses of 10, 50, and 100 µg g–1 of 4-nonylphenol, as well as 2 µg g–1 of 17β-estradiol (E2) via intraperitoneal injection. The negative control group received a solvent mixture (ethanol and olive oil) with no injections. Fish sampling for blood and liver analysis occurred on days 0, 7, and 14. After RNA extraction from liver tissue and cDNA synthesis, variations in Vg expression were analyzed in relation to the beta-actin gene. The results showed a significant increase in Vg expression in the treatment groups compared to control groups. Sequencing confirmed the presence of the Vg gene, with a fragment size of 174 nucleotides. Additionally, plasma levels of sexual steroid hormones were measured using radiomonoactivity, which revealed a decrease in testosterone levels associated with varying concentrations of 4-nonylphenol. In contrast, E2 levels in fish exposed to 4-nonylphenol increased after 7 and 14 days. The findings suggest that exposure to 4-nonylphenol activates Vg production, potentially adversely affecting puberty, sexual development, sexual behaviors, and reproductive success in Sobaity seabream.